The gender gap in competitiveness: Women shy away from competing with others, but not from competing with themselves - Johanna Mollerstrom; Katharina Wrohlich (DIW Economic Bulletin, 2017)
Women are less willing than men to compete against others. This gender gap can partially explain the differences between women's and men's education and career choices, and the labor market disparities that result. The experiments presented here show that even though women are less willing than men to compete against others, they are just as willing as men are to take on the challenge of improving themselves and competing against their own past performance. For organizations striving towards gender equality, this opens up new possibilities for institutionalizing competitive pressure.
Keywords: C90; C91; J16; J71; 330; gender; competition; discrimination; experiment